Return of the Temujai - Flanagan, John (John Anthony) (Flanagan, John (John Anthony). Brotherband chronicles, 2019)
"The Herons are home in Skandia, but the usually peaceful country is in danger. The Temujai--ruthless warriors from the Eastern Steppes--have never given up on their ambition to claim Skandia for their own...and now they're on the move. Hal and his crew will have to brave the treacherous icy river and rapids to stop them, no matter the cost"--Amazon.com.